1991
DOI: 10.1007/bf00291150
|View full text |Cite
|
Sign up to set email alerts
|

Relation between serological data at the time of biopsy and renal histology in lupus nephritis

Abstract: As autoantibodies are thought to participate in the pathogenesis of renal inflammation in systemic lupus erythematosis (SLE) we investigated associations between serological markers of disease activity in SLE and the activity of renal histopathological lesions in thirty-five patients with lupus nephritis (LN). We found the following prevalence of serum auto-antibodies in LN: IgG antinuclear antibodies (ANA) 100%, IgM ANA 69%, IgA ANA 60%, IgG anti-dsDNA 60%, IgM anti-dsDNA 71%, IgA anti-dsDNA 60%, anti-RNP 20%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 34 publications
0
24
1
Order By: Relevance
“…In addition, one study [9] reported an association with lupus nephritis, whereas another study [11] concluded that there was an association with active nephritis only. We set out to test the hypothesis that IgA anti-dsDNA antibodies are associated with disease activity and clinical manifestations of SLE in a large population of SLE patients.…”
Section: Introductionmentioning
confidence: 97%
“…In addition, one study [9] reported an association with lupus nephritis, whereas another study [11] concluded that there was an association with active nephritis only. We set out to test the hypothesis that IgA anti-dsDNA antibodies are associated with disease activity and clinical manifestations of SLE in a large population of SLE patients.…”
Section: Introductionmentioning
confidence: 97%
“…Silent LN has been reported not only in class II but also in class IV (62)(63)(64)(65)(66)(67)(68). Even patients with low-level proteinuria (,1 g/24 h) have demonstrated significant renal involvement with proliferative LN (classes III or IV) (69,70).…”
Section: Clinicopathologic Correlationsmentioning
confidence: 99%
“…eases such as SLE (2,3), mixed connective tissue disease (4) and Sj6gren's syndrome (5). Some authors addressed the possible role of IgG-and IgM-aCL as indicators of clinical activity in SLE (3,(6)(7)(8)(9). However, it remains uncertain in which rheumatic diseases and under what conditions monitoring of aCL is clinically useful.…”
Section: Introductionmentioning
confidence: 97%